2007
DOI: 10.1007/s00417-007-0671-9
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of neurite outgrowth and protective effect of erythropoietin on the retinal neurons of rats

Abstract: EPO had a significant biological effect on neurite outgrowth of the dissociated retinal neurocytes in vitro. EPO was beneficial in promoting the survival and decreasing the apoptosis rates of the cultured retinal neurocytes suffering from glutamate-induced cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In cells that involve the brain or the retina, EPO can prevent injury from hypoxic ischemia (Chong et al, 2002b;Liu et al, 2006;Meloni et al, 2006;Wei et al, 2006;Yu et al, 2005), excitotoxicity (Montero et al, 2007;Yamasaki et al, 2005), infection (Kaiser et al, 2006), free radical exposure Chong et al, 2003e;Yamasaki et al, 2005), staurosporine (Pregi et al, 2006), and dopaminergic cell injury (Demers et al, 2005;McLeod et al, 2006;Signore et al, 2006). In addition, administration of EPO also represents a viable option for the prevention of retinal cell injury during glutamate toxicity (Zhong et al, 2007) and glaucoma (Tsai et al, 2007). Systemic application of EPO also can improve functional outcome and reduce cell loss during spinal cord injury (King et al, 2007;Okutan et al, 2007), traumatic cerebral edema (Verdonck et al, 2007), cortical trauma (Cherian et al, 2007), and epileptic activity (Mikati et al, 2007;Nadam et al, 2007).…”
Section: Epo and Neurodegenerationmentioning
confidence: 99%
“…In cells that involve the brain or the retina, EPO can prevent injury from hypoxic ischemia (Chong et al, 2002b;Liu et al, 2006;Meloni et al, 2006;Wei et al, 2006;Yu et al, 2005), excitotoxicity (Montero et al, 2007;Yamasaki et al, 2005), infection (Kaiser et al, 2006), free radical exposure Chong et al, 2003e;Yamasaki et al, 2005), staurosporine (Pregi et al, 2006), and dopaminergic cell injury (Demers et al, 2005;McLeod et al, 2006;Signore et al, 2006). In addition, administration of EPO also represents a viable option for the prevention of retinal cell injury during glutamate toxicity (Zhong et al, 2007) and glaucoma (Tsai et al, 2007). Systemic application of EPO also can improve functional outcome and reduce cell loss during spinal cord injury (King et al, 2007;Okutan et al, 2007), traumatic cerebral edema (Verdonck et al, 2007), cortical trauma (Cherian et al, 2007), and epileptic activity (Mikati et al, 2007;Nadam et al, 2007).…”
Section: Epo and Neurodegenerationmentioning
confidence: 99%
“…Our previous studies demonstrated that EPO had a neuroprotective effect in vivo (15) and a neurite outgrowth promotion effect on retinal neurons in vitro (23). However, the mechanism of the axonal regeneration effect of EPO on retinal neurons has not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal explants in the control group were continually cultured with serum-free R16 nutrient medium; the retinal explants in the glutamate group were continually cultured with serum-free R16 nutrient medium containing 5 mM/l glutamate (Sigma-Aldrich, St. Louis, MO, USA); and the retinal explants in the glutamate + EPO group were continually cultured with serum-free R16 nutrient medium containing 5 mM/l glutamate and 6.0 U/ml EPO. The retinal explants in the three groups were continually cultured for another 72 h. The doses of glutamate and EPO used in the present study were selected according to our previous study in which it was shown that 6.0 U/ml EPO significantly improved the survival of cultured retinal neurocytes incubated with 5 mM/l glutamate (23).…”
Section: Methodsmentioning
confidence: 99%
“…In cells that involve the brain or the retina, EPO can prevent injury from hypoxic ischemia [45,110,[225][226][227], excitotoxicity [228,229], infection [230], free radical exposure [61, 105,229], amyloid exposure [112], staurosporine [231], and dopaminergic cell injury [232]. In addition, administration of EPO also represents a viable option for the prevention of retinal cell injury during glutamate toxicity [233] and glaucoma [234]. Systemic application of EPO also can improve functional outcome and reduce cell loss during spinal cord injury [235,236], traumatic cerebral edema [237], cortical trauma [238], and epileptic activity [211,239].…”
Section: Erythropoietin a Cytokine And Growth Factormentioning
confidence: 99%